Analisis Efektivitas dan Kontribusi Penerimaan Pajak Bumi dan Bangunan Terhadap Pendapatan Asli Daerah Kota Bandung - Astri Nur Fauziah; Onoy Rohaeni (UPT Publikasi Universitas Islam Bandung, 2025)
The Bandung City Regional Revenue Agency (Bapenda) with the Land and Building Tax sub-section basically always applies certain targets in the realization of the taxes received. Targets are established by calculating achievements per year, which are evaluated at the end of the year. However, every year the targets from the UN are not always met. Thus, it is necessary to analyze the effectiveness level of Land and Building Tax revenues and discover the role of PBB in increasing Regional Original Income (PAD), one of which is by looking at how big its contribution is. In making this article, the aim is to discover the effectiveness level of PBB revenue and the contribution of PBB to PAD from 2016 to 2022. The results obtained are that the average effectiveness of revenue reaches 90.59%, if measured by the effectiveness criteria then Land Tax revenue and Building (UN) effective. And the PBB contribution to PAD is with an average contribution of 21.22%. If measured by criteria, the Land and Building Tax (PBB) contribution revenue to Bandung City's Regional Original Income (PAD) is moderate.